PROMOTING MIND-MAPPING TECHNIQUE TO IMPROVE NURSING STUDENTS’ WRITING SKILL - Febrijanto, Yoyok (English Education:Journal of English Teaching and Research, 2016)
A teacher can use many ways to make students easier to study writing. Mind-mapping is a way to solve problems in writing. This technique is chosen since it has many advantages. The main benefit is that it uses both halves of the brain which makes it easier to remember. Moreover, making mind-mapping is a creative process and a natural way to organize the thoughts and it is widely believed to ease a pathway towards successful communication. Nursing students mostly do not pay attention to their writing skill. There are some indications which show the students’ poor ability in writing, such as; the students do not organize their writing well, their ideas are not coherence, they do not use right tenses in the right context, they have lack of vocabulary and their understanding of mechanic is low. They also think that time for writing is limited. Because of these, they become unmotivated and have low interest in writing. Some students even give up and do not try to solve their problem. In this paper, the writer wants to describe the use of mind-mapping technique to build up a good writing practice as an alternative teaching learning process and to activate the students’ participation in the classroom. Keywords: Mind-Mapping Technique, Writing Skill.